INLAND WATERWAYS TRANSPORT IN THE EUROPEAN UNION - FLOWING OR STILL STANDING? (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Although the inland waterways transport (transport/navigation on rivers, lakes and canals) is, by its characteristics, an acceptable mode of transport, in some EU member states it is still unfortunately underestimated and insufficiently exploited. Cost-effectiveness, safety and eco-friendliness are the main characteristics of the inland waterway transport. The European Union emphasizes the reduction of traffic congestion, increased traffic safety, the use of environmentally friendly modes of transport and the use of alternative fuels as the goals of its transport policy. Developed inland waterway transport is therefore one of the possible solutions for the achievement of these goals. European Union has some 40,000 km of navigable waterways and 13 Member States have an interconnected waterway network, which is a great potential for the development of this mode of transport.Although the European Union has provided a number of programmes and actions for inland waterway transport to encourage it and to increase the share of goods and passengers transported by inland waterways, the major results appear to be absent. The paper presents the significance and potential of EU inland waterway transport, relevant sources of law and their implementation, as well as activities and results of work in the field of inland waterway transport.